Association between DHEAS and bone loss in postmenopausal women: a 15-year longitudinal population-based study. - Ghebre, M; Hart, D; Hakim, A; Kato, B; Thompson, V; Arden, N; Spector, T; Zhai, G (2011)
Our aim was to examine the association between serum dehydroepiandrosterone sulfate (DHEAS) at baseline and BMD change at the femoral neck (FN) and lumbar spine (LS) in postmenopausal women during a 15-year follow-up. All participants were from the Chingford Study. BMD at the FN and LS were measured eight times during the 15-year follow-up by dual-energy X-ray absorptiometry. DHEAS at baseline was measured using radioimmunoassay. Data on height, weight, and hormone-replacement therapy (HRT) status were obtained at each visit. Multilevel linear regression modeling was used to examine the association between longitudinal BMD change at the FN and LS and DHEAS at baseline. Postmenopausal women (n = 1,003) aged 45-68 years (mean 54.7) at baseline were included in the study. After adjustment for baseline age, estradiol, HRT, and BMI, BMD at the FN decreased on average 0.49% (95% CI 0.31-0.71%) per year; and the decline was slowed down by 0.028% per squared year. Increase of DHEAS (each micromole per liter) was associated with 0.49% less bone loss at the FN (95% CI 0.21-0.71%, P = 0.001). However, this strong association became slightly weaker over time. Similar but weaker results were obtained for LS BMD. Our data suggest that high serum DHEAS at baseline is associated with less bone loss at both FN and LS and this association diminishes over time. The nature of the association is unclear, but such an association implies that, in managing BMD loss, women might benefit from maintaining a high level of DHEAS.